Study on the deterioration trend of the rock mass on the reservoir banks under dry-wet cycles - Gao, Xuecheng; Wang, Luqi; Xiang, Yuzhou; Jiang, Xiang; Yang, Yang; Ran, Bo (Frontiers in Ecology and Evolution, 2022)
The deterioration of rock mass under dynamic mechanical state is difficult to determine, especially when evolution trends of micro-fractures are considered. Taking the limestone from Wuxia section of the Three Gorges Reservoir area as studying case, cross-scale tests and theoretical analysis were adopted to study the influence of dry-wet cycles on rock deterioration. The weakly acidic condition (pH=6) and the dry environment at 105°C were together constituted the two extreme mechanical states of the dry-wet cycles. Meanwhile, the number of dry-wet cycles and soaking time were used as the main variables to analyze the deterioration trend. After introducing the damage mechanics, the quantitative relationship between the mechanical parameters and changing mechanical states was obtained. Combined with the microstructure obtained by scanning electron microscope (SEM), it can be found that with the increase of dry-wet cycles and soaking time, the morphology of mineral particles changed, the number of secondary pores gradually increased, the surface structure became looser, and the microcracks gradually increased, causing the decrease of macro strength. The related method proposed in this paper could provide significant references to determine the mechanical parameters of rocky reservoir bank.